PENGARUH RIGHT ISSUE, KEBIJAKAN DIVIDEN, DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PERUSAHAAN PELAYARAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Azizah, Elok Tri Nur; Pandin, Maria Yovita R. (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2024)
One of the ways companies use to issue shares is by means of a rights issue. A right issue is an alternative for companies that have gone public in raising funds in the capital market. To achieve the desired company growth, the company establishes a dividend policy, namely a policy made by the company to determine the proportion of income distributed as dividends paid. While EPS is a ratio that measures the amount of dividends per share that will be distributed to investors after deducting dividends for company owners. The research objectives to be achieved in accordance with the formulation of the problem described above are to determine and analyze the effect of partial and simultaneous rights issues, dividend policy, and earnings per share (EPS) on stock prices. In this study the method used is quantitative method with descriptive analysis techniques, and the population is shipping companies listed on the Indonesia Stock Exchange (IDX). Sampling used in this study is purposive sampling. The analysis technique used is multiple linear regression analysis. The findings of the analysis conclude that all rights issue variables, dividend policy, and earnings per share (X1, X2, X3) have a significant effect on stock prices (Y).